Hepatitis C virus activates a Neuregulin-driven circuit to modify surface expression of growth factor receptors of the ErbB family - Stindt, Sabine; Bartenschlager, Ralf (PLOS ONE, 2016)
Recently, the epidermal growth factor (EGF) receptor (EGFR), a member of the ErbB receptor family, and its down-stream signalling have been identified as co-factors for HCV entry and replication. Since EGFR also functions as a heterodimer with other ErbB receptor family members, the subject of the present study was to investigate a possible viral interference with these cellular components. By using genotype 1b replicon cells as well as an infection-based system we found that while transcript and protein levels of EGFR and ErbB2 were up-regulated or unaffected, respectively, HCV induced a substantial reduction of ErbB3 and ErbB4 expression. Down-regulation of ErbB3 expression by HCV involves specificity protein (Sp)1-mediated induction of Neuregulin (NRG)1 expression as well as activation of Akt. Consistently, at transcript level disruption of ErbB3 expression by HCV can be prevented by knockdown of NRG1 or Sp1 expression, whereas reconstitution of ErbB3 protein levels requires inhibition of HCV-induced NRG1 expression and of Akt activity. Interestingly, the NRG1-mediated suppression of ErbB3 expression by HCV results in an enhanced expression of EGFR and ErbB2 on the cell surface, which can be mimicked by siRNA-mediated knockdown of ErbB3 expression. These data delineate a novel mechanism enabling HCV to sway the composition of the ErbB family members on the surface of its host cell by an NRG1-driven circuit and unravels a yet unknown cross-regulation between ErbB3 and the two other family members ErbB2 and EGFR. The shift of the receptor surface expression of the ErbB family towards enhanced expression of ErbB2 and EGFR triggered by HCV was found to promote viral RNA replication and infectivity. This suggests that HCV rearranges expression of ErbB family members to adapt the cellular environment to its requirements.